The Red-crested Pochard Netta rufina breeding and wintering in Yugoslavia - Schneider-Jacoby, Martin; VasiÄ‡, Vojislav F (Wildfowl, 1989)
The breeding of Red-crested Pochard was proved in the Posavina (Croatia) in 1987, the birds probably originating in Central Europe where the population is healthy with flocks of nonbreeding birds at, for instance, Lake Constance and Lake Neusiedl. The large numbers of Red-crested Pochard found in January 1987, 1988 and 1989 on Lake Ohrid (Macedonia), which is a good wintering site because of the occurrence of Chara, are likely to be part of the Eastern European population.